Expressive Writing to Relieve Academic Stress at University Level - Juanita Argudo (Universidad Nacional de Colombia, 2021)
This paper reports on a descriptive mixed-method study that aimed to identify the impact of expressive writing on relieving the academic stress of 157 undergraduate students at an Ecuadorian university. Data were gathered through two questionnaires and from focus groups. Results showed enduring relief of academic stress. Furthermore, they help to shed light on the need to study the impact of academic stress on university students and to look for different strategies that can alleviate it. These findings could help to understand students' needs, as they have essential implications in teachers' practices and, consequently, in students' performance. In conclusion, expressive writing has a positive effect on helping to ease academic stress and overcome some difficulties caused by this issue.